America's Fight over Water : the Environment and Political Effects of Large-Scale Water. - Wehr, Kevin (Routledge, 2004)
This book inquires into the relations between society and its natural environment by examining the historical discourse around several cases of state building in the American West - the construction of three high dams from 1928 to 1963.